Population biology of shrimp Macrobrachium jelskii (Miers, 1778) (Decapoda, Palaemonoidea) at the Grande River at northwest of the state of Minas Gerais, Brazil - Barros-Alves, Samara de Paiva [UNESP]; Almeida, Ariádine Cristine [UNESP]; Fransozo, Vivian; Alves, Douglas Fernandes Rodrigues [UNESP]; Silva, José Carlos da; Cobo, Valter José (Associação Brasileira de Limnologia, 2012)
OBJETIVO: A biologia populacional do camarão de água doce Macrobrachium jelskii foi investigada, com ênfase na distribuição de frequência em classes de tamanho, razão sexual, período reprodutivo e recrutamento juvenil. Além disso, a abundância dos indivíduos foi correlacionada com os fatores abióticos. MÉTODOS: Amostras foram coletadas mensalmente de julho de 2005 a junho de 2007, às margens do Rio Grande, região de Planura, estado de Minas Gerais, Brasil (20º 09' S e 48º 40' W), usando uma rede de arrasto (1.0 mm tamanho da malha e 2.0 × 0.5 m de largura). O equipamento foi arrastado por duas pessoas às margens da vegetação do rio por 100 metros de distância, percorridos por uma hora. em laboratório, os espécimes foram identificados, mensurados e sexados. RESULTADOS: Um total de 2,789 espécimes foi analisado, no qual correspondem a 1,126 machos (549 jovens e 577 adultos) e 1,663 fêmeas (1,093 jovens, 423 adultos não ovígeras e 147 ovígeras). A razão sexual diferiu significativamente a favor de fêmeas de M. jelskii (1:1.48; χ² = 103.95; p < 0.0001). A média de tamanho do comprimento da carapaça (CL) das fêmeas (6.32 ± 1.84 mm CL) foi estatisticamente maior do que dos machos (5.50 ± 1.07 mm CL) (p < 0.001). A distribuição de freqüência em classes de tamanho dos espécimes revela um padrão de distribuição unimodal e não normal para machos e fêmeas (W = 0.945; p < 0.01). Não foi observada relação entre a abundância de M. jelskii e as variáveis ambientais (p = 0.799). CONCLUSÃO: A presença de fêmeas ovígeras e jovens na população sugere um padrão de reprodução e recrutamento contínuos para M. jelskii na região de Planura.

AIM: The population biology of the freshwater shrimp Macrobrachium jelskii was investigated here emphasizing the length-frequency distribution, sex ratio, reproductive period and juvenile recruitment. In addition, the abundance of individuals was correlated with the abiotic factors. METHODS: Samples were collected on a monthly basis from July 2005 to June 2007 along the river margin in shallow water of Grande River, at Planura region, State of Minas Gerais, Brazil (20º 09' S and 48º 40' W), using a trawl net (1.0 mm mesh size, and 2.0 m × 0.5 m wide). The fishing gear was handled by two people along the marginal vegetation of the Grande River in a course of 100 m, covered for one hour. In the laboratory, the specimens were identified, measured and sexed. RESULTS: A total of 2,789 specimens was analyzed, which corresponded to 1,126 males (549 juveniles and 577 adults) and 1,663 females (1,093 juveniles, 423 adults non-ovigerous and 147 ovigerous). The sex ratio differed significantly in favor of the females of M. jelskii (1:1.48; χ² = 103.95; p < 0.0001). The mean size of carapace length (CL) of females (6.32 ± 1.84 mm CL) was statistically higher than of males (5.50 ± 1.07 mm CL) (p < 0.001). The length-frequency distribution of the specimens revealed an unimodal pattern and non-normal distribution for males and females (W = 0.945; p < 0.01). No significant relationship between the abundance of M. jelskii and the environmental variables was observed (p = 0.799). CONCLUSION: The presence of ovigerous females and juveniles in the population suggests a continuous reproduction pattern and recruitment for M. jelskii at Planura region.
Biologia populacional do camarão Macrobrachium jelskii (Miers, 1778) (Decapoda, Palaemonoidea) no Rio Grande no noroeste do estado de Minas Gerais, Brasil
Keywords: Caridea; distribuição; recrutamento juvenil; período reprodutivo; razão sexual; Caridea; distribution; juvenile recruitment; reproductive period; sex ratio